Rumah Sebagai Garda Depan Pertahanan Masyarakat Selama Pandemi Covid-19: Pengukuran Resiliensi Kawasan Permukiman di Indonesia - Rahmawati, Dian; Umilia, Ema; Idajati, Hertiari; Fortuna, Shellyn (Universitas Diponegoro, Indonesia, 2021)
Various prevention and adaptations have been carried out to prevent the recent global pandemic of COVID-19, one of which is encouraging people to do activities at homes to reduce the level of transmission of the COVID-19 virus. Worker and students adapted to working from home (WFH) and learning from home (LFH) which resonates globally with the hashtag stayhome. This policy is quite effective if we assume that all residential areas have ideal conditions to accommodate the health functions and productivity of their residents. In fact, housing and settlement areas in Indonesia have various characteristics and responses to pandemic situations. This article aims to map the adaptation efforts of housing and settlement areas in Indonesia during the COVID-19 pandemic based on several observational variables. Data was taken in May 2020, the 3rd month after the appeal to stay home was socialized in Indonesia, through 110 respondents who were undergoing WFH and LFH, spread across almost all parts of Indonesia. The data is processed through descriptive statistical analysis and the results show that the assumption that all residential areas are in a state that is ready to become the frontline of defense during the pandemic has not been as expected, especially from observations of houses and their surroundings as a function of isolation, the effectiveness of implementing rules and policies, and limitation of activities in order to increase settlement resilience.